Reduction in emergency room visits with cenobamate in pharmaco-resistant epilepsy: an observational study - Gal Khazin; Nir Hersh; Aida Hleihil; Ilan Goldberg; Felix Benninger (Brain Disorders)
Objective: Cenobamate (Xcopri) is an antiepileptic drug introduced in Israel in July 2023 that has shown promise in reducing seizure frequency in patients with focal seizures.This study aims to evaluate the real-world effectiveness and safety of Cenobamate in a clinical setting, providing insights into its impact on quality of life and its side effect profile. Methods: This observational cross-sectional study was conducted at Beilinson Hospital, Rabin Medical Center, involving a cohort of 54 pharmaco-resistant epilepsy patients. Treatment durations ranged from 58 to 422 days (mean: 168.6 days), and doses ranged from 12.5 mg to 300 mg (mean: 146.1 mg). We evaluated the effectiveness and safety of Cenobamate by assessing seizure reduction, side effects, and changes in various biochemical parameters. Data on electrolytes and emergency room visits before and after starting Cenobamate were analysed for 47 patients. Results: Cenobamate demonstrated significant efficacy in reducing seizures, with an average seizure reduction of 57.5 ± 41 %. Seizure freedom was achieved in 27.5 % of patients in the Intention to Treat (ITT) analysis and in 43.8 % of patients on doses greater than 200mg. 35 % of patients experienced side effects, including headache, dizziness, tiredness, sleep disturbances, and mood changes, with a discontinuation rate of 14.8 %. A significant reduction in average emergency room visits from 1.53 to 0.534 per year (p < 0.0001, -65.1 %) was noted. Creatinine levels (p = 0.0005, +6.5 %) as well as potassium levels (p = 0.0323, +5.6 %) increased mildly but significantly. A trend towards increased liver enzyme levels was also noted, suggesting further investigation is needed. Significance: Cenobamate treatment in our cohort was associated with a significant reduction in emergency room visits, indicating its potential benefit in managing pharmaco-resistant epilepsy. However, it also resulted in a slight increase in potassium and a significant increase in creatinine levels, along with a trend towards increased liver enzyme levels. These findings suggest the need for further investigation into the long-term safety profile of Cenobamate. Limitations of our study include the cohort size, as well as some participants having short treatment durations, possibly contributing to misleading results.